Legislative Elections: an Overview of Closed Proportional System - Mutawalli, Muhammad; M., Maskun; Ayub, Zainal Amin; Tajuddin, Muhammad Saleh; Abdul Wahab, Harlida (Lembaga Kajian Konstitusi Indonesia (LKKI), 2023)
This study aims to analyze the constitutionality of legislative general elections with a review of the closed proportional system in the 1945 Constitution. The legislative election system is an important tool for maintaining democratic principles and fair representation in a country. The constitutionality of the closed proportional system has been the subject of ongoing debate. This study uses a qualitative approach with normative juridical methods to analyze the constitutionality of general legislative elections that use a closed proportional system. This approach involved collecting data from legal documents, literature studies, and court decisions that were relevant to this topic. The results of the study showed that the application of a closed proportional system in legislative general elections has several constitutional implications, such as the limitation of political access for individuals outside of political parties, which can be considered as a violation of the individual’s constitutional right to participate in the political process. This research also showed that a closed proportional system can provide greater political stability and strengthen the role of political parties in the political system. This study also analyzed the implications of implementing an open proportional system in legislative general elections